Strategi kepala sekolah dalam pengembangan kompetensi profesional guru untuk meningkatkan mutu pendidikan - Wimbawarni, Wiwik; Sutanto, Agus; Dacholfany, Ihsan (STIES ALIFA, 2021)
Professional competence is the ability to master material broadly and deeply, and guide students by meeting the competency standards set in national education standards. Competencies that must be met include 4 competencies, namely: a. Pedagogical competence; b. Personality competence; c. Professional competence; and D. Social Competence. More detailed provisions are set out in Permendiknas No. 16 of 2007 concerning AcademicQualifications and Teacher Competencies. Regarding the work of teachers explained in Law No. 14 of 2005 article 1 as follows: